A composite material for periodontitis sequential therapy medicine and a preparation method thereof
Patent Information
- Application Number
- CN202611274904.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有技术中尚缺乏一种既能实现牙周炎早期局部抗炎,又能在后期促进牙槽骨再生修复的时序功能型生物医用材料
(1)本发明的复合材料包括PLLA/MgO支撑层和负载GsMTx4的水凝胶层,其中,负载GsMTx4的水凝胶层主要作用于修复早期,通过调控局部炎症微环境、减轻炎症反应,为后续组织修复创造有利条件;PLLA/MgO支撑层则在后续阶段提供必要的结构支撑,并发挥促骨再生作用。前者改善微环境,后者促进组织重建,二者在时间维度和功能维度上形成有机衔接,实现牙周炎病灶局部治疗中早期抗炎和后期骨再生的功能分离与协同。
Smart Images

Figure CN122894341A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a composite material for sequential treatment of periodontitis and its preparation method. Background Technology
[0002] Periodontitis is a chronic destructive disease mediated by plaque microbial infection and host inflammatory response. It can lead to gingivitis, loss of periodontal attachment, and alveolar bone resorption, and in severe cases, tooth loosening or even loss. For patients with periodontitis accompanied by alveolar bone resorption and destruction of periodontal supporting tissues, basic treatment alone is often insufficient to achieve simultaneous improvement in inflammation control and tissue regeneration.
[0003] Current treatments for periodontitis include scaling, root planing, root planing, topical medication, and periodontal surgery. While topical anti-inflammatory or antibacterial drugs can improve the inflammatory response to some extent, they are difficult to sustain in the complex periodontal microenvironment and have limited effectiveness in repairing existing alveolar bone defects. On the other hand, although bone repair materials and guided tissue regeneration membranes can be used for periodontal regeneration therapy, their regeneration effectiveness is easily affected when the inflammatory microenvironment is not effectively controlled.
[0004] In recent years, biomedical materials have received widespread attention in the field of periodontal regeneration. However, current technologies lack a time-series functional biomedical material that can achieve both early local anti-inflammatory effects in periodontitis and promote alveolar bone regeneration and repair in later stages. Therefore, developing a biomedical material with a rational structure, well-defined function, and suitability for local periodontal application is of great significance. Summary of the Invention
[0005] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a composite material for sequential treatment of periodontitis and a method for preparing the same. This composite material simultaneously possesses the functions of early local anti-inflammatory effects in periodontitis, late alveolar bone regeneration and repair, and periodontal tissue-guided regeneration, and is suitable for preparing sequential treatment drugs for periodontitis.
[0006] To solve the above-mentioned technical problems, the first aspect of the present invention provides a composite material comprising a support layer and a hydrogel layer stacked together, wherein the support layer is prepared from PLLA (poly-L-lactic acid) and MgO, and the surface of the support layer is coated with a dopamine hydrophilic modification layer; the hydrogel layer is loaded with GsMTx4.
[0007] Specifically, the composite material of this invention comprises a PLLA / MgO support layer and a GsMTx4-loaded hydrogel layer. GsMTx4 is a polypeptide that regulates abnormal signals associated with mechanosensitive ion channels. Periodontitis lesions not only exhibit inflammatory responses but also abnormal mechanical stimulation, changes in tissue tension, and imbalances in related signals. Therefore, this invention utilizes a specific GsMTx4, which, compared to traditional anti-inflammatory polypeptides, better matches the pathological characteristics of the "inflammation-mechanical abnormality" coupling in periodontitis. The GsMTx4-loaded hydrogel layer can act in the early stages of repair, regulating the local inflammatory microenvironment and reducing the inflammatory response, thus creating favorable conditions for subsequent tissue repair. PLLA possesses good biocompatibility, biodegradability, and mechanical support properties. Magnesium oxide (MgO), as a bioactive inorganic component, can release magnesium ions and regulate the local microenvironment, promoting cell adhesion, proliferation, and osteogenic differentiation. This invention combines PLLA and MgO to provide necessary structural support in subsequent stages and promote bone regeneration. This invention improves the microenvironment through a GsMTx4-loaded hydrogel layer and promotes tissue regeneration through a PLLA / MgO support layer, forming an organic connection between the two in both time and functional dimensions. In vitro and in vivo experimental results show that, compared with using the PLLA / MgO support layer or the GsMTx4-loaded hydrogel layer alone, the bilayer composite system constructed in this invention exhibits superior effects in inflammation regulation, tissue repair, and bone regeneration, demonstrating a synergistic repair effect.
[0008] Meanwhile, the PLLA-based support layer has a relatively hydrophobic surface and limited surface active sites, while the GsMTx4-loaded hydrogel precursor system is highly hydrophilic, resulting in significant differences in interfacial wettability and compatibility. Directly applying the hydrogel layer to the PLLA / MgO support layer surface can easily lead to uneven spreading of the hydrogel precursor solution, insufficient interfacial adhesion, and unstable interlayer bonding after curing. This can cause hydrogel layer detachment, delamination, or interfacial instability during immersion in body fluids, handling, or implantation, affecting the overall structural integrity of the material and its sustained repair function. Furthermore, the bilayer material needs to balance two different functions: early anti-inflammatory regulation in the upper layer and late-stage bone-supporting development in the lower layer. An improperly constructed interface can not only weaken the effective connection between the functions of each layer but may also affect the achievement of sequential treatment effects. To address this, the present invention modifies the PLLA / MgO support layer with dopamine to improve the wettability and interfacial activity of the PLLA / MgO support layer surface, thereby promoting the uniform spreading of the GsMTx4-loaded hydrogel precursor liquid on its surface and further forming a stable interfacial adhesion with the PLLA surface fiber network, thus improving the overall stability of the bilayer structure during in vivo and in vitro use.
[0009] In some embodiments of the present invention, the MgO can be nanoparticles, microparticles, or nanosheets with an average particle size of 10 nm to 50 μm; for example, it can be any particle size or a range between any two of 10 nm, 50 nm, 100 nm, 200 nm, 500 nm, 800 nm, 1 μm, 5 μm, 10 μm, 30 μm, and 50 μm.
[0010] In some embodiments of the present invention, the mass ratio of PLLA to MgO is 100:(1-50); for example, it can be any mass ratio or any range of mass ratios between 100:1, 100:2, 100:5, 100:10, 100:20, 100:30, 100:40, 100:50.
[0011] In some embodiments of the present invention, the hydrogel substrate in the hydrogel layer is selected from at least one of gelatin, methacrylamide gelatin, hyaluronic acid, alginate, chitosan, polyethylene glycol, and fibroin.
[0012] In some embodiments of the present invention, the loading concentration of GsMTx4 in the hydrogel layer is 0.1-10 mg / mL; for example, it can be any loading concentration of 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 3 mg / mL, 5 mg / mL, 8 mg / mL, 10 mg / mL or any range of loading concentrations between the two.
[0013] In some embodiments of the present invention, the thickness of the support layer is 100-200 μm; for example, it can be any thickness of 100 μm, 120 μm, 140 μm, 150 μm, 160 μm, 180 μm, 200 μm or any range between two of them.
[0014] In some embodiments of the present invention, the thickness of the hydrogel layer is 20-100 μm. For example, it can be any thickness of 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm or any range between two of these.
[0015] In some embodiments of the invention, the hydrogel layer is located on the side facing the periodontal inflamed soft tissue, and the support layer is located on the side facing the bone defect.
[0016] In some embodiments of the present invention, the composite material may be in the form of a film, patch, sponge, block, or other local implantation form adapted to the shape of periodontal pockets.
[0017] In some embodiments of the present invention, the structure of the support layer can be a porous membrane, a fiber membrane, a porous scaffold, or a dense-porous composite structure.
[0018] A second aspect of the present invention provides a method for preparing the composite material described in the first aspect of the present invention, comprising the following steps: MgO particles are dispersed in a PLLA solution to prepare a mixture; then the mixture is used to form a PLLA / MgO composite membrane, i.e., a support layer. A hydrogel precursor solution loaded with GsMTx4 was prepared by mixing the hydrogel precursor solution, photoinitiator and GsMTx4. The support layer is immersed in a dopamine solution to form a dopamine hydrophilic modified layer on the surface of the support layer; The hydrogel precursor liquid loaded with GsMTx4 was coated onto the surface of the dopamine hydrophilic modified layer and then photocured to obtain the composite material.
[0019] In some embodiments of the present invention, the concentration of the dopamine solution is 0.5-2.0 g / L; for example, it can be any concentration of 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, or any concentration range between two of them.
[0020] In some embodiments of the present invention, the soaking time is 1-3 hours.
[0021] In some embodiments of the present invention, the light source for photocuring is blue light.
[0022] In some embodiments of the present invention, the photocuring time is 20-40 seconds. Photocuring allows the hydrogel to gel in situ on the surface of the support layer, thereby creating a more stable interfacial bonding region between the two layers. This significantly reduces the risk of hydrogel detachment and interlayer separation, further improving the overall stability of the bilayer structure during in vivo and in vitro use.
[0023] In some embodiments of the present invention, the photoinitiator may be a photoinitiator commonly used in the art, typically but not limitingly, such as LAP (lithium phenyl-2,4,6-trimethylbenzoylphosphine).
[0024] In some embodiments of the present invention, the amount of photoinitiator is 0.1-0.5 wt% of the hydrogel precursor solution.
[0025] In some embodiments of the present invention, the PLLA / MgO composite membrane is prepared by electrospinning or solution casting of the mixture.
[0026] In some embodiments of the present invention, the concentration of the PLLA solution is 5-25 wt%; for example, it can be any concentration or a range of both of 5 wt%, 10 wt%, 15 wt%, 20 wt%, and 25 wt%.
[0027] In some embodiments of the present invention, the solvent for the PLLA solution may be a commonly used organic solvent in the art, typically but not limitingly, such as hexafluoroisopropanol.
[0028] In some embodiments of the present invention, the concentration of the hydrogel precursor solution is 5-20 wt%; for example, it can be any concentration or a concentration range of any two of 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, and 20 wt%.
[0029] A third aspect of the present invention provides the use of the composite material described in the first aspect of the present invention in the preparation of a sequential treatment drug for periodontitis.
[0030] In some embodiments of the present invention, the composite material is used in the preparation of anti-inflammatory drugs for periodontitis.
[0031] In some embodiments of the present invention, the composite material is used in the preparation of alveolar bone defect repair drugs.
[0032] In some embodiments of the present invention, the composite material is used in the preparation of a drug for periodontal tissue-guided regeneration.
[0033] Compared with the prior art, the above-described technical solution of the present invention has at least the following technical effects or advantages: (1) The composite material of the present invention comprises a PLLA / MgO support layer and a GsMTx4-loaded hydrogel layer. The GsMTx4-loaded hydrogel layer mainly acts in the early stage of repair, by regulating the local inflammatory microenvironment and reducing the inflammatory response, thus creating favorable conditions for subsequent tissue repair. The PLLA / MgO support layer provides necessary structural support in the later stage and plays a role in promoting bone regeneration. The former improves the microenvironment, and the latter promotes tissue reconstruction. The two form an organic connection in the temporal and functional dimensions, realizing the functional separation and synergy of early anti-inflammatory and late bone regeneration in the local treatment of periodontal lesions.
[0034] (2) This invention employs a combination of dopamine surface modification and in-situ photocuring. First, a dopamine-modified layer with strong adhesion is formed on the surface of the PLLA / MgO support layer, improving the wettability and interfacial activity of the support layer surface. This facilitates the uniform spreading of the GsMTx4-loaded hydrogel precursor liquid on its surface and further forms a stable interfacial adhesion with the surface fiber network of the support layer. Simultaneously, photocuring allows the hydrogel to gel in situ on the electrospun membrane surface, thereby constructing a relatively stable interfacial bonding region between the two layers. This significantly reduces the risk of hydrogel detachment and interlayer separation, improving the overall stability of the bilayer structure during in vivo and in vitro use.
[0035] (3) The composite material of the present invention has a double-layer structure design. The hydrogel layer loaded with GsMTx4 can release active molecules in the early stage of implantation, improve the inflammatory microenvironment and reduce the inflammatory response; the PLLA / MgO support layer has good mechanical support and biological activity, which is conducive to maintaining the defect space and promoting alveolar bone regeneration; the double-layer structure helps to reduce the mutual interference between different functional components and improve the local treatment effect; it can be applied to the preparation of periodontitis sequential treatment drugs such as periodontitis, alveolar bone defect repair and periodontal tissue guided regeneration. Attached Figure Description
[0036] Figure 1 SEM images and EDS spectra of the fiber membranes prepared in Examples 1-2 and Comparative Examples 5-6; Figure 2 SEM image of the composite material prepared in Example 1; Figure 3 The graph shows the anti-inflammatory evaluation results of the composite materials prepared in Example 1 and Comparative Examples 1-3; Figure 4 The image shows the in vitro osteogenic evaluation results of the PLLA / MgO support layer prepared in Example 1. Figure 5 The graph shows the in vivo repair-promoting evaluation results of the composite materials prepared in Example 1 and Comparative Examples 2-4. Detailed Implementation
[0037] The present invention will now be described in detail with reference to embodiments to facilitate understanding of the invention by those skilled in the art. It is particularly important to note that the embodiments are merely illustrative of the invention and should not be construed as limiting the scope of protection of the invention. Non-essential improvements and adjustments made to the invention by those skilled in the art based on the above description should still fall within the scope of protection of the invention. Furthermore, all raw materials mentioned below, unless otherwise specified, are commercially available products; all process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.
[0038] Some of the raw materials used in the following examples and comparative examples are as follows: PLLA: Henan Saihou Biotechnology Co., Ltd., 26811-96-1; Photoinitiator LAP: Engineering for Life, 85073-19-4; GsMTx4: MCE, HY-P1410; Dopamine: Maclean, A902400; Osteogenic culture medium: including 10 -810 mmol / L dexamethasone, 50 μmol / L vitamin C, 10 mmol / L β-glycerol phosphate, high glucose medium (Gibco) rich in 10% FBS. The synthesis process of methacrylamide gelatin is as follows: 5 g of type B gelatin (Sigma Aldrich) was dissolved at 10% w / v in sodium carbonate-sodium bicarbonate (CB) buffer (0.25 mol / L, pH adjusted to 9.0) and heated to 55°C. Then, 500 μL of methacrylic anhydride (Aladdin, 94%) was added to the gelatin solution in six portions, reacting for 3 h with continuous stirring. The reaction was then terminated by adjusting the pH to 7.4. The resulting solution was filtered through a 0.22 μm antibacterial filter membrane and then dialyzed for one week at 37°C using a dialysis membrane with a molecular weight cutoff (MWCO) of 12,000-14,000 Da. After dialysis, the solution was placed in a suitable container. The product was incubated overnight at 80°C, followed by freeze-drying to obtain the final dried GelMA product.
[0039] Example 1 A method for preparing a composite material includes the following steps: (1) Preparation of PLLA / MgO support layer: PLLA was dissolved in hexafluoroisopropanol to prepare a 12wt% PLLA solution. Then, MgO particles (average particle size 100nm) were added to the PLLA solution at 10wt% of the PLLA mass. After ultrasonic dispersion and mechanical stirring, a homogeneous PLLA / MgO mixture was obtained. The PLLA / MgO mixture was then electrospun (voltage: 10-12kV, flow rate: 1-3mL / h) to prepare a PLLA / MgO fiber membrane, i.e., the support layer. The fiber diameter of the PLLA / MgO fiber membrane was 500nm-2μm.
[0040] (2) Preparation of hydrogel precursor solution loaded with GsMTx4 Methacrylated gelatin was dissolved in PBS buffer to obtain a 10 wt% hydrogel precursor solution. Photoinitiator LAP was added at a concentration of 0.25 wt% of the hydrogel precursor solution, and the mixture was stirred until homogeneous. Then, GsMTx4 was added and mixed to obtain a GsMTx4-loaded hydrogel precursor solution. The loading concentration of GsMTx4 in the hydrogel precursor solution was 5 mg / mL.
[0041] (3) Preparation of composite materials The PLLA / MgO fiber membrane obtained in step (1) was immersed in a dopamine solution with a concentration of 1.0 mg / mL for 2 hours to coat the surface of the PLLA / MgO fiber membrane with a dopamine hydrophilic modification layer. Then, the PLLA / MgO fiber membrane coated with the dopamine hydrophilic modification layer was laid flat in a mold. The GsMTx4-loaded hydrogel precursor solution obtained in step (2) was then uniformly coated on the surface of the PLLA / MgO fiber membrane. Finally, it was irradiated with 405 nm blue light for 30 seconds to crosslink into a gel, forming a GsMTx4-loaded hydrogel layer, thus obtaining the composite material of this embodiment. Wherein, the thickness of the GsMTx4-loaded hydrogel layer is 60 μm, and the thickness of the PLLA / MgO fiber membrane layer is 150 μm.
[0042] Example 2 Referring to the preparation method of the composite material in Example 1, only the amount of MgO particles (average particle size of 100 nm) added in step (1) was changed to 5 wt% of the mass of PLLA.
[0043] Example 3 The method for preparing the composite material in Example 1 was used as a reference, except that the amount of MgO particles (average particle size of 100 nm) added in step (1) was changed to 2.5 wt% of the mass of PLLA.
[0044] Comparative Example 1 The hydrogel loaded with GsMTx4 prepared in Example 1.
[0045] Comparative Example 2 Referring to the preparation of the PLLA / MgO support layer in Example 1, no MgO particles were added during the preparation process to obtain the PLLA fiber membrane.
[0046] Comparative Example 3 The PLLA / MgO fiber membrane prepared in Example 1.
[0047] Comparative Example 4 Commercially available HEAL-ALL oral film.
[0048] Comparative Example 5 PLLA was dissolved in hexafluoroisopropanol to prepare a PLLA solution with a mass concentration of 15wt%; then, disordered PLLA fiber membrane (RPLLA) was prepared by electrospinning the PLLA solution (voltage: 10-12kV, flow rate: 1-2mL / h, rotation speed: 400rpm).
[0049] Comparative Example 6 PLLA was dissolved in hexafluoroisopropanol to prepare a PLLA solution with a mass concentration of 15wt%; then, the PLLA solution was electrospinned (voltage: 10-12kV, flow rate: 1-2mL / h, rotation speed: 2800rpm) to obtain an ordered PLLA fiber membrane (APLLA).
[0050] Structural characterization and performance evaluation 1. Structural Characterization Figure 1 SEM images and EDS spectra of the PLLA / MgO fiber membranes prepared for Examples 1 (10% MgO), 2 (5% MgO), and 3 (2.5% MgO), as well as the fiber membranes prepared for Comparative Example 5 (RPLLA) and Comparative Example 6 (APLLA). Figure 1 As can be seen from the present invention, ordered PLLA electrospun films with parallel arrangement can be prepared, and magnesium oxide can be successfully spun on PLLA electrospun films.
[0051] Figure 2 The image shows a cross-sectional SEM image of the composite material prepared in Example 1. It is clear from the image that the composite material has a bilayer structure.
[0052] 2. Evaluation of in vitro anti-inflammatory properties An inflammation model was established using lipopolysaccharide (LPS)-stimulated macrophages (RAW264.7) for 24 hours. Materials prepared in Examples 1, 1, 2, and 3 were co-cultured with the inflammation model, resulting in the LPS+PMG group, LPS+GsMTx4 group, LPS+PLLA group, and LPS+PLLA / MgO group, respectively. These were compared with the LPS group and the normal control group (Control). The expression levels of inflammatory factors IL-1β, IL-6, and TNF-α in each group were detected. The results are shown below. Figure 3 Parts (a), (b), and (c) of the text. Figure 3 It can be seen that the GsMTx4-loaded bilayer composite material prepared in Example 1 can reduce the expression level of inflammatory factors in LPS-induced macrophages (RAW264.7), indicating that it has a good in vitro anti-inflammatory effect.
[0053] 3. In vitro evaluation of osteogenic properties The disordered and ordered PLLA fibers prepared in Comparative Examples 5 and 6, respectively, were spun onto PLLA / MgO fiber membranes prepared in Example 1 and placed on 18 mm circular glass slides. Bone marrow mesenchymal stem cells (BMSCs) and periodontal ligament stem cells (PDLSCs) were then seeded onto the surface of each fiber membrane, designated as the RPLLA group, APLLA group, and PLLA / MgO group, respectively, and compared with a blank control group. Cell viability was assessed using live / dead staining. After 7 days of culture in osteogenic differentiation medium, alkaline phosphatase activity and osteogenic-related indicators such as RUNX2, ALP, and SP7 were measured. The results are as follows: Figure 4 As shown in (a)-(d) of the diagram. Figure 4 It is known that the PLLA / MgO fiber membrane prepared by this invention can promote osteogenic differentiation of periodontal ligament stem cells and bone marrow mesenchymal stem cells.
[0054] 4. Evaluation of animal experiments A periodontitis model was established by binding SD rats with No. 3 surgical sutures for 4 weeks. Materials prepared in Examples 1, 2, 3, and 4 were then co-cultured with the inflammation model, designated as the PMG group, PLLA group, PLLA / MgO group, and Heal-All group (positive control group), respectively. These were compared with the periodontitis blank group (Sham) and the normal control group (Control). Two weeks after successful model establishment, the inflammation level, alveolar bone repair degree, and periodontal tissue regeneration were assessed. Results are as follows: Figure 5 As shown. By Figure 5 As can be seen from part (a) of the present invention, the composite material prepared by the present invention can significantly promote alveolar bone regeneration. Figure 5 Parts (b) and (c) show the results of statistical analysis using two methods: bone loss area and CEJ-ABC distance. The results indicate that the bilayer composite material has a more significant therapeutic effect than the positive control group.
[0055] For those skilled in the art, several simple deductions or substitutions can be made without departing from the inventive concept, without requiring creative effort. Therefore, any simple improvements made to this invention by those skilled in the art based on the disclosure of this invention should be within the scope of protection of this invention. The above embodiments are preferred embodiments of this invention, and all processes similar to this invention and equivalent changes should fall within the scope of protection of this invention.
Claims
1. A composite material, characterized in that, It includes a support layer and a hydrogel layer stacked together. The support layer is prepared from PLLA and MgO. The surface of the support layer is coated with a dopamine hydrophilic modification layer. The hydrogel layer is loaded with GsMTx4.
2. The composite material according to claim 1, characterized in that, The average particle size of the MgO is 10 nm to 50 μm; and / or the mass ratio of the PLLA to MgO is 100:(1-50).
3. The composite material according to claim 1, characterized in that, The hydrogel substrate in the hydrogel layer is selected from at least one of gelatin, methacrylated gelatin, hyaluronic acid, alginate, chitosan, polyethylene glycol, and fibrin; and / or the loading concentration of GsMTx4 in the hydrogel layer is 0.1-10 mg / mL.
4. The composite material according to claim 1, characterized in that, The thickness of the support layer is 100-200 μm; and / or, the thickness of the hydrogel layer is 20-100 μm.
5. A method for preparing the composite material according to any one of claims 1-4, characterized in that, Includes the following steps: MgO particles are dispersed in a PLLA solution to prepare a mixture; then the mixture is used to form a PLLA / MgO composite membrane, i.e., a support layer. A hydrogel precursor solution loaded with GsMTx4 was prepared by mixing the hydrogel precursor solution, photoinitiator and GsMTx4. The support layer is immersed in a dopamine solution to form a dopamine hydrophilic modified layer on the surface of the support layer; The hydrogel precursor liquid loaded with GsMTx4 was coated onto the surface of the dopamine hydrophilic modified layer and then photocured to obtain the composite material.
6. The method for preparing the composite material according to claim 5, characterized in that, The concentration of the dopamine solution is 0.5-2 g / L; and / or, the soaking time is 1-3 hours.
7. The method for preparing the composite material according to claim 5, characterized in that, The light source for photocuring is blue light; and / or the photocuring time is 20-40 seconds.
8. The method for preparing the composite material according to claim 5, characterized in that, The PLLA / MgO composite membrane is prepared by electrospinning or solution casting of the mixture.
9. The method for preparing the composite material according to claim 5, characterized in that, The concentration of the PLLA solution is 5-25 wt%; and / or the concentration of the hydrogel precursor solution is 5-20 wt%.
10. The use of the composite material according to any one of claims 1-4 in the preparation of a sequential treatment drug for periodontitis.